Donorsite defect of medial femoral condyle corticoperiostal flap in the treatment of lower limb infected nonunions - Guzzini, Matteo; Arioli, Leopoldo; Rugiero, Clelia; Rossini, Marco; Argento, Giuseppe; Ferretti, Andrea (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
Backgrounds Chronic osteomyelitis is a major challenge in orthopaedic surgery; it is the result of open fracture, periprosthetic infection and septic arthritis. Osteomyelitis leads to fracture nonunion. The treatment of bone infection and infected nonunion consists primarily of the complete removal of infected and avascular bone and soft tissue from the surgical site, followed by local and systemic pathogen-specific antibiotic therapy and temporary stabilisation, but may lead to massive skeletal and soft tissue defects. The use of free or pedicled vascularised bone transfers and callus distraction techniques (bone transport) has been recommended for large bone defects. The aim of this study is to evaluate the results of patients affected by infected non-unions of the lower limbs, treated with a corticoperiosteal flap from the medial femoral condyle and to investigate the donor site morbidity of this flap.Materials and methods The patients were 11 males (average age of 45.6 years), who presented a nonunion of the tibial diaphysis in 7 cases and non-union of femoral diaphysis in 4 cases, treated with free or pedicled corticoperiosteal flap. In all patients, surgical debridement was performed before the flap of infected bone and soft tissues that would not contribute to wound healing. Clinical and radiographic evaluations of the recipient site were performed. Preoperative and postoperative X-ray and MRI scans after the 3-year follow-up of the donor site were performed, in order to observe possible bone restoration and any complications.Results The patients reported complete clinical and radiographic bone healing in 90.9 % of cases. As regards donor site, there were no differences between the medial femoral donor condyle compared to the contralateral site, due to complete regeneration of donor site bone. MRI investigation showed complete restoration of the donor site with vascularised bone in all patients.Conclusions Our results suggest that the use of bone flaps for the treatment of infected non-unions is an effective procedure, that must be performed after accurate debridement of the non-union site. The corticoperiosteal flap seems to have few morbidities on the donor site and a high percentage of successful bone healing.
Keywords: Nonunion; corticoperiosteal; flap; infected; lower limb